Integrasi Analisis Bibliometrik Scopus–VOSviewer dan Simulasi Diskrit (ProModel) dalam Evaluasi Kinerja Distribusi Drone Last-Mile - Ahyar, Ok Rangga; Parinduri, Putri; Fadhillah, Rahmat; Solin, Syarifuddin; Aulia, Khairul Nizan (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The results of the co-occurrence, co-authorship, and citation analyses indicate that existing studies predominantly emphasize technical development, artificial intelligence integration, communication systems, and sustainability aspects, while quantitative operational performance modeling remains limited. Based on the identified research gaps, a discrete event simulation model was developed in promodel to represent operational processes, including order reception, routing, loading, flight operations, battery charging or swapping, and return cycles. Several policy scenarios were tested by varying fleet size, charging station capacity, and demand patterns. Simulation results demonstrate that system performance is significantly influenced by charging infrastructure capacity, resource allocation, and scheduling configuration, directly affecting delivery time, throughput, and drone utilization. The integration of bibliometric mapping and simulation modeling provides a comprehensive decision-support framework that bridges conceptual research trends with practical operational optimization in last-mile drone logistics.